Core–shell tecto dendrimers formed via host–guest supramolecular assembly as pH-responsive intelligent carriers for enhanced anticancer drug delivery - Wang, Jianhong; Li, Du; Fan, Yu; Shi, Menghan; Yang, Yunxia; Wang, Le; Peng, Yitian; Shen, Mingwu; Shi, Xiangyang (Nanoscale, 2019)
The design of pH-sensitive supramolecular drug delivery systems for efficient antineoplastic drug delivery remains a huge challenge. Herein, we describe the development of pH-responsive core–shell tecto dendrimers (CSTDs) formed using benzimidazole (BM)-modified generation 3 (G3) poly(amidoamine) (PAMAM) dendrimers (G3.NHAc-BM) as a shell and β-cyclodextrin (CD)-modified G5 PAMAM dendrimers (G5.NHAc-CD) as a core. By virtue of the host–guest recognition and pH-responsiveness of BM/β-CD assembly, the pH-sensitive supramolecular CSTDs of G5.NHAc-CD/BM-G3.NHAc were formed and adopted to encapsulate the anticancer drug doxorubicin (DOX) via hydrophobic interactions for pH-responsive drug delivery applications. The synthesis of dendrimer derivatives and the loading of the DOX were well characterized via different methods. We show that the encapsulated DOX can be released in a sustained manner with a rapid release speed under a slightly acidic pH condition (pH < 6), which is similar to acidic tumor microenvironment. The enhanced intracellular release of DOX and improved anticancer activity of the drug-loaded pH-responsive CSTDs were demonstrated and compared with the control CSTDs formed without pH-responsiveness through flow cytometry and viability assays of cancer cells. Furthermore, the pH-sensitive CSTDs also showed efficient drug penetration and growth inhibition of three-dimensional tumor spheroids owing to the faster DOX release in an acidic pH environment. The pH-sensitive G5.NHAc-CD/BM-G3.NHAc CSTDs may be employed as a valuable intelligent delivery system for various anticancer drugs.